From concept to monument : time and costs of construction in the ancient world : papers in honour of Janet Delaine - Barker, Simon J.,; Courault, Christopher,; Domingo Magaña, Javier Á., 1978-; Maschek, Dominik,; DeLaine, Janet, (Archaeopress Archaeology, 2023)
21 papers focus on modelling the costs of construction over the course of 2500 years, from Bronze Age Greece to the early Middle Ages. They discuss both broader issues of methodology and particular case studies, with particular attention to the exploitation of raw materials (e.g. quarries), transport, and construction processes on building sites.